Association between serum calcium, serum phosphate and aortic stenosis with implications for prevention. (March 2018) - Wald, David S; Bestwick, Jonathan P
Background: Aortic stenosis is the most common cause of valvular heart disease with no means of prevention. Lowering serum levels of calcium or phosphate are potential preventive strategies but observational studies on the associations with aortic stenosis are inconsistent. Design and methods: A case–control study was conducted in 132 individuals undergoing echocardiography (63 with aortic stenosis and 69 without) and the results combined with three other comparable studies (914 individuals overall) to provide a summary odds ratio of aortic stenosis for a 0.1 mmol/L increase (approximately one standard deviation) in calcium and phosphate respectively. The relationship between calcium and phosphate and the severity of aortic stenosis, according to peak trans-aortic velocity, was also examined in the case–control study using linear regression. Results: Both calcium and phosphate were positively associated with aortic stenosis. The summary odds ratio for a 0.1 mmol/L increase in calcium was 1.79 (95% confidence interval 1.07–2.99), p = 0.027 and for phosphate it was 1.47 (1.08–2.01), p = 0.015. Peak trans-aortic velocity increased with phosphate levels, 9% (4%–14%) per 0.1 mmol/L, p = 0.001, but not with calcium, p = 0.089. Conclusions: If the associations are causal and reversible, these results indicate that a small reduction in calcium or phosphate levels, within the physiological rage, would translate into a clinically significant reduction in the risk of aortic stenosis. Randomised trials of calcium and phosphate lowering therapies in aortic stenosis are needed.